Influence of Tungsten Inert Gas Welding on Hardness, Tensile Strength and Microstructures of Aluminum 6061 Alloy Weldments - Musa, A. A.; Mohammed, M. A.; Dauda, E. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
In this work, tungsten inert gas (TIG) welding was used for joining aluminum 6061 alloy because it offers low heat input to the weld joints and the ability to remove any refractory oxides such as Al2O3 through a process known as the cathodic cleaning effect. This research was carried out to evaluate the level of improvement in the tensile strength and the hardness of aluminum 6061 alloy welds, using a tungsten inert gas welding approach. Aluminum 6061 alloy in form of a round bar of length 100 mm and 8 mm in diameter was first machined to the standard tensile testing specimen according to the American society for testing and materials (ASTM) using a lathe machine. It was then butt welded along the center of the bar using tungsten inert gas welding process with a constant welding current of 18 Amperes and gas flow rate of 15 liter/min. the same process was repeated for both the hardness and microstructure specimens followed by butt welding along the center of the specimen. The welded samples were then subjected to the hardness and tensile testing using Rockwell hardness testing and Hounsfield tensile testing machine respectively. The results showed that the welded metal and the heat-affected zone possessed the highest hardness value of 84.2 HRB and 71.9 HRB respectively as compared with the parent metal with a hardness value of 66.8 HRB. Also, the tensile strength of the welded specimens is 300.35 N/mm² which is relatively lower than that of the base material with a tensile strength of 348.67 N/mm². Additionally, the results of the microstructural examination reveal the presence of trace aluminum oxides within the matrix of the welded structure which indicates the slight increase observed in the hardness of the welded sample as compare to that of the base material. Therefore, the hardness and tensile strength for the welded sample are close to the base metal indicating that welding of aluminum and its alloys using the TIG welding process gives welds of adequate mechanical properties.